Emergency Pavilion : Rebuilding Utopia. - Castro, Jota; Biennale di Venezia Venice 2013 ([S.l.] : Ultra & The Emergency Pavilion, 2013)
de Burca, Ella ; Castro, Jota ; Hamilton, Patrick ; Jacir, Emily ; Marcelle, Cinthia ; Margolles, Teresa ; Prieto, Wilfredo ; Sierra, Santiago ; Tacla, Jorge
Collateral event of the 55th International Art Exhibition la Biennale di Venezia, Teatro Fondamenta Nuove, Venice, June 1st - November 10th, 2013
kunstcatalogus